EXPLAINING SYNONYMY BETWEEN OBLIGATION EXPRESSIONS IN FINNISH LEGAL LANGUAGE – RESULTS OF A SURVEY - RYDZEWSKA-SIEMIĄTKOWSKA, Joanna (Comparative Legilinguistics, 2016)
The aim of this research is to examine synonymy between two obligation expressions, tulee and on -t(t)ava, in Finnish legal language on the basis of the results of a survey. The analysis is based on the responses of 336 Finnish language users. Both expressions are the most frequent means of expressing obligation in normative acts and they can be regarded as near-synonyms. However, the synonymy between them has not been studied in legal language so far. On the basis of respondents’ comments ten differentiating features have been found. The features distinguished in the research can provide some additional information on the usage of the expressions because not all of the features have been addressed in the dictionaries so far.